Extreme Outliers in Lower Stratospheric Water Vapor Over North America Observed by MLS Relation to Overshooting Convection Diagnosed From Colocated Aqua-MODIS Data - Werner, F (Geophysical research letters, 2020)
©2020. The Authors.